2022
DOI: 10.3390/plants11131712
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Spectral Indices for High-Throughput Phenotyping

Abstract: The conventional plant breeding evaluation of large sets of plant phenotypes with precision and speed is very challenging. Thus, consistent, automated, multifaceted, and high-throughput phenotyping (HTP) technologies are becoming increasingly significant as tools to aid conventional breeding programs to develop genetically improved crops. With rapid technological advancement, various vegetation indices (VIs) have been developed. These VI-based imaging approaches, linked with artificial intelligence and a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 126 publications
0
8
0
1
Order By: Relevance
“…Furthermore, this type of information can be used as a secondary trait for indirect selection and prediction of the target trait by exploiting the correlation between the traits (Rutkoski et al, 2016; Sun et al, 2017). In addition, spectral vegetation indices (SVI) can provide information about plant status and development (Tayade et al, 2022) and previous studies suggested that SVI calculated from HTP could increase the efficiency of indirect selection for seed yield and can be integrated into sesame breeding programs (Petsoulas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this type of information can be used as a secondary trait for indirect selection and prediction of the target trait by exploiting the correlation between the traits (Rutkoski et al, 2016; Sun et al, 2017). In addition, spectral vegetation indices (SVI) can provide information about plant status and development (Tayade et al, 2022) and previous studies suggested that SVI calculated from HTP could increase the efficiency of indirect selection for seed yield and can be integrated into sesame breeding programs (Petsoulas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is grown and consumed throughout the year because it has numerous health-promoting compounds, such as anthocyanins, carotenoids, chlorophylls, flavonoids, hydroxycinnamic acid derivatives, isorhamnetin, kaempferol, phenolics, quercetin, vitamins, and minerals. 2,3 Glucosinolates are a large group of plant secondary metabolites with nutritional effects and biological activity. Glucosinolates are primarily found in cruciferous plants, including the widely consumed Brassicaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Most VIs are ratios or linear combinations of spectral reflectance in two or more wavelength bands [ 39 ] that can be obtained from HSI [ 37 , 40 ]. Consisting of a straightforward transformation of spectral bands, VIs are estimated without bias or presumptions about land cover class, soil type, or climate conditions—enabling the observations of seasonal and long-term changes in a vegetation’s structural, phenological, and biophysical characteristics [ 41 , 42 , 43 ]. VIs have proven to be a valuable tool for monitoring plant health and productivity, and they are widely applied in fields such as agriculture, forestry, and ecology.…”
Section: Introductionmentioning
confidence: 99%